New π-electron deficient molecular materials and their photo/redox properties - Malagreca, Ferdinando (2024)
Diketopyrrolopyrrole (DPP) pigment and dyes are an increasingly investigated family of organic materials with applications ranging from organic optoelectronics to sensor materials and bio imaging, amongst others. The main goal of this thesis is to design and synthesise new small molecule diketopyrrolopyrrole (DPP). In order to achieve this goal, DPP functionalized with pyridine, pyridinium, benzaldehyde and benzoate aromatic units have been synthesized. Those feature means that the materials are extremely electron deficient in nature and are very good electron acceptors. Each aromatic ring allowed to tune and modulate electron richness character of the molecule, this means that each of it has different redox potentials and different optical properties. To investigate their properties, electrochemical experiments have been carried out, especially cyclic voltammetry in order to determine each systems frontier orbital energy levels and exploring the electron accepting properties of the molecules, ultraviolet-visible absorption spectroelectrochemistry providing molecular information related to the electronic levels of molecules and to determinate different parameters such as absorptivity coefficients, diffusion coefficients, formal potentials or electron transfer rates and the stability of the molecules, Absorption and emission spectroscopy to determinate the optical properties in the ground and excited state. After studying their fundamental properties, some those molecules have been tested for different applications. These novel electron-accepting DPPs proved to have good applications as redox mediator in batteries and as photo-catalyst.